The neglected potential of invertebrates in detecting disease via olfaction - Piqueret, Baptiste; Sandoz, Jean-Christophe; d’Ettorre, Patrizia (Frontiers in Ecology and Evolution, 2023)
Agents that cause disease alter the cell metabolism of their hosts. Cells with an altered metabolism produce particular profiles of biomolecules, which are different from those of healthy cells. Such differences may be detected by olfaction. Historically, physicians used olfactory cues to diagnose sickness by smelling the breath or the urine of patients. However, other species have been shown to possess excellent olfactory abilities. Dogs, for instance, have been frequently used as biodetectors of human diseases, including cancer, viral and bacterial infections. Other mammalian species, such as rats, have been trained to perform similar tasks, but their disease detection abilities remain poorly explored. Here, we focus on the overlooked potential of invertebrate species and we review the current literature on olfactory detection of diseases by these animals. We discuss the possible advantages of exploring further the abilities of invertebrates as detection tools for human disease.